ChemInform Abstract: (Diacetoxyiodo)benzene‐Mediated Oxygenation of Benzylic C(sp3)‐H Bonds with N‐Hydroxyamides at Room Temperature. Issue 28 (July 2015) - Qian, Peng‐Cheng; Liu, Yu; Song, Ren‐Jie; Hu, Ming; Yang, Xu‐Heng; Xiang, Jian‐Nan; Li, Jin‐Heng
Abstract A new and general, catalyst‐free strategy for the formation of C(sp3)—O bonds is established by iodosobenzene diacetate‐mediated oxygenation of benzylic C(sp3)—H bonds with N‐hydroxyamides.